Super obese 33-week parturient undergoing an urgent laparoscopic bowel resection: A case report and review of anesthetic implications - Yury Khelemsky; Danielle M Gluck (Wolters Kluwer Medknow Publications, 2011)
Approximately two percent of women undergo non-obstetric surgery during their pregnancies. The following case report describes the anesthetic management of a super obese parturient in her third trimester of pregnancy undergoing urgent laparoscopic (converted to open) bowel resection. Such a case, which has not been previously reported, has multiple clinical implications for both mother and fetus and was further complicated by super obesity (BMI>50) and laparoscopy. The anesthetic implications for this patient population are reviewed.